THE CSRD DIRECTIVE AND ESRS STANDARDS AS INSTRUMENTS FOR ENSURING TRANSPARENCY UNDER THE EUROPEAN GREEN DEAL - Kruhla, Maryna; Lezhnenko Lіudmyla; Kruhlyi, Vladyslav (Current Problems of Sustainable Development, 2026)
The article provides a comprehensive theoretical and analytical study of the Corporate Sustainability Reporting Directive (CSRD) (EU) 2022/2464 and the European Sustainability Reporting Standards (ESRS) as key instruments for corporate transparency within the implementation of the European Green Deal strategy. The research explores the historical prerequisites for the transition from the fragmented and descriptive Non-Financial Reporting Directive (NFRD) to the more rigorous, mandatory regulatory requirements of the CSRD. The authors reveal the essence of the innovative paradigm of double materiality, which forms the core of the new methodology. The paper details the structure of the IROs framework (impacts, risks, and opportunities) analyzed across significance and probability scales, as well as the architecture of the twelve sector-agnostic ESRS standards covering environmental (E1–E5), social (S1–S4), and governance (G1) aspects. Special attention is paid to the requirements for mandatory digital tagging of reported data using the Inline XBRL format and the transition from limited assurance to a stricter reasonable assurance of sustainability disclosures under the new International Standard on Assurance Engagements ISSA 5000. Based on global and domestic academic discussions, the article evaluates the long-term strategic opportunities for the European capital market and identifies key structural challenges faced by companies. These include excessive regulatory burden, non-financial data quality gaps, high deployment costs of ESG accounting systems, and the persistent risks of formal compliance, often referred to as greenwashing. Finally, the study highlights the prospects, deep methodological challenges, and practical significance of implementing the CSRD/ESRS provisions in Ukraine. In the context of European integration commitments and the post-war recovery based on green growth, adopting these standards is identified as a strategic foundation for Ukrainian enterprises, particularly in the agricultural sector, to secure direct access to international financial capital and seamlessly integrate into global value chains. To achieve this, the authors emphasize the critical need to overcome the shortage of skilled ESG auditors, modernize digital IT infrastructure for accounting, and establish technical cooperation with EFRAG to account for the wartime specificities of the national economy. The study systematizes the structural components of the “Strategy for the Introduction of Sustainability Reporting by Enterprises” in Ukraine and identifies the institutional mechanisms for its practical implementation.